1996
DOI: 10.1111/j.1468-0092.1996.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the British Late Upper Palaeolithic: New Evidence for Chronological Patterning in the Lateglacial Record

Abstract: Summary. Variation in Lateglacial lithic assemblages has led some researchers to sub‐divide the British Later Upper Palaeolithic into two or more typologically distinct phases (Campbell 1977; Jacobi 1988). Until now, however, the chronological relationships between the different phases have been difficult to demonstrate. In this paper we present new dating evidence for two distinct blade technologies of Lateglacial type found in southwest Britain. The first corresponds to the ‘Creswellian’(as defined by Jacob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…In recent publications (Jacobi, 1991(Jacobi, , 1997Jacobi and Roberts, 1992;Barton and Roberts, 1996;Barton, 1999) the diagnostic importance of the bi-truncated Cheddar point has been reaffirmed and it has been suggested that the term Creswellian should be reserved for assemblages that share most or all of the following characteristics: 1 trapezoidal backed blades with a double truncation (Cheddar points) and backed forms with a single truncation (Creswell points); 2 end-scrapers on long blades, the lateral edges often being modified by retouch; 3 burins, mostly on prepared truncations; 4 piercers and becs; 5 Magdalenian blades (with scalariform retouch), truncated blades with heavily worn or 'rubbed' ends (lames tronquées et usées) and splintered pieces (pièces esquillées); 6 well-made blades and bladelets, detached from cores with a single preferred flaking direction. Features on the ventral surface indicate a predominance of the soft hammer mode of percussion.…”
Section: Reassessing the Chronology Of The British Late-glacialmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent publications (Jacobi, 1991(Jacobi, , 1997Jacobi and Roberts, 1992;Barton and Roberts, 1996;Barton, 1999) the diagnostic importance of the bi-truncated Cheddar point has been reaffirmed and it has been suggested that the term Creswellian should be reserved for assemblages that share most or all of the following characteristics: 1 trapezoidal backed blades with a double truncation (Cheddar points) and backed forms with a single truncation (Creswell points); 2 end-scrapers on long blades, the lateral edges often being modified by retouch; 3 burins, mostly on prepared truncations; 4 piercers and becs; 5 Magdalenian blades (with scalariform retouch), truncated blades with heavily worn or 'rubbed' ends (lames tronquées et usées) and splintered pieces (pièces esquillées); 6 well-made blades and bladelets, detached from cores with a single preferred flaking direction. Features on the ventral surface indicate a predominance of the soft hammer mode of percussion.…”
Section: Reassessing the Chronology Of The British Late-glacialmentioning
confidence: 99%
“…The most significant of these are the microlithic backed bladelets that typify the Late Magdalenian on the east and south of the North Sea basin, in areas immediately adjacent to the British Isles. Equally, we would argue that the curve-backed points typical of mainland Final Palaeolithic Azilian and Federmesser assemblages would not form part of LATE-GLACIAL REOCCUPATION OF THE BRITISH ISLES 633 the Creswellian lithic inventory (Barton and Roberts, 1996). It follows then that the rare presence of 'penknife points' and other curve-backed elements at British sites with Creswellian assemblages is undoubtedly due to mixing of the Creswellian with material from younger contexts.…”
Section: Reassessing the Chronology Of The British Late-glacialmentioning
confidence: 99%
See 3 more Smart Citations